1996
DOI: 10.1182/blood.v87.6.2538.bloodjournal8762538
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary spherocytosis with spectrin deficiency due to an unstable truncated beta spectrin

Abstract: Red cell membrane protein analysis by sodium dodecyl sulfate- polyacrylamide gel electrophoresis (SDS-PAGE) and direct quantitation by radioimmunoassay or cytofluorometry defines four distinct subsets of patients with hereditary spherocytosis: Patients with isolated spectrin deficiency, combined spectrin and ankyrin deficiency, band 3 deficiency, and protein 4.2 deficiency. In regard to the first group, only one mutation of beta spectrin has been reported in the literature. We describe a spectrin variant chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…In this study, four patients from two families with non-HS showed mutations in spectrin tetramer (SPTA1 p.Arg41Trp and SPTB p.Phe2014Val) and homozygous SPTB mutation revealed HPP whereas heterozygous SPTA1 one revealed HE. Several patients harboring SPTB mutations on domain outside of tetramer were initially misreported as HS and self-corrected as HE by the researchers (42,43). A comprehensive literature review reinforced the finding that mutations in spectrin tetramer are associated with HE or HPP and mutant dosage (heterozygous and homozygous) affects the disease phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, four patients from two families with non-HS showed mutations in spectrin tetramer (SPTA1 p.Arg41Trp and SPTB p.Phe2014Val) and homozygous SPTB mutation revealed HPP whereas heterozygous SPTA1 one revealed HE. Several patients harboring SPTB mutations on domain outside of tetramer were initially misreported as HS and self-corrected as HE by the researchers (42,43). A comprehensive literature review reinforced the finding that mutations in spectrin tetramer are associated with HE or HPP and mutant dosage (heterozygous and homozygous) affects the disease phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Relative mRNA quantification of red cell membrane protein genes in Polish patients indicated that SPTB could be involved in anaemia pathogenesis. Most of the SPTB gene defects identified so far are splicing, frameshift and nonsense mutations that lead to transcript instability or truncation of the spectrin β protein (Dhermy et al , 1998; Hassoun et al , 1996, 1997). With the exception of some polymorphic amino acid changes, no common mutation has been described.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several mutations in SPTB have been discovered and their effects studied in detail (Gallagher & Forget, 1998). These include various missense, as well as splicing, frameshift and nonsense mutations, that usually result in mRNA processing defects and truncated spectrin β variants (Dhermy et al , 1998; Hassoun et al , 1996, 1997). The currently known HS‐associated SPTB changes are scattered all over the SPTB gene, which is over 100 kb in length and consists of 32 exons (Iolascon et al , 1998; Maillet et al , 1996).…”
mentioning
confidence: 99%
“…Deficiency of protein 4·2 has been reported, but it is less common in western populations (Gallagher et al , 1998). β‐spectrin‐related HS is relatively common (Becker et al , 1993; Hassoun et al , 1995, 1996, 1997; Garbarz et al , 1998; Bassères et al , 1998; Dhermy et al , 1998), and is frequently a result of null mutations, in which the mutant mRNA is unstable and the allele is not expressed (Hassoun et al , 1997; Dhermy et al , 1998; Miraglia del Giudice et al , 1998). One other characteristic feature of β‐spectrin‐related dominant HS is the presence of acanthocytes in the blood smear (Hassoun et al , 1997).…”
mentioning
confidence: 99%